CRENÇAS E DISCURSOS DE PROFESSORES DO ENSINO FUNDAMENTAL SOBRE LEITURA DE TEXTOS LITERÁRIOS EM ESCOLAS PÚBLICAS DE SANTA MARIA - Flores, Alexandre Roberto Camillo (2022)
The beliefs and discourses of teachers about readings of texts go through the process of academic background, intricate guidelines and documents that guide, regulate, and define the main knowledge for the process of teaching and learning in the country. In this context the dissertation has the intention to investigate what are the teacher´s beliefs of Elementary public schools in Santa Maria, Rio Grande do Sul, about the reading of literary texts. Further, to identify and describe the conceptions in the education level, for the emersion of belief categories and to discuss the implications of these beliefs for the teaching of literary texts in basic education. The dissertation approaches the subject of research about teaching and teacher practices of the master language and humanities teaching from Universidade Franciscana, for its investigations relate to the teaching and learning processes of languages. Qualitative approach is the research method, lined from the analysis of questionaries and interviews addressed to teachers, for this the research characterization is through an Exploratory Analysis of Critical Discourse Analysis grounded by Norman Fairclough and the Portuguese Systemic Functional Grammar. With the research results, after the questionaries and interviews analysis, it was understood the difficulties faced by teachers as well as their practices and beliefs about literary texts in the classroom. After the analysis of the answers and its conclusions all the participant teachers believe that the reading of literary texts is an important practice in the classroom and the main categories of beliefs that were emerged by them were the ones related to its utility function, the socializing function and the literary emotional function.